المعاني لأفعال الحواس الخمس في السياق القرآني وتضمينها التربوي - Zulli Umri Siregar (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2013)
This study departed from the notion that the meanings of words in the Qur’an are bounded by the context. Words of similar meaning in general actually have significant differences. Words related to the five senses, for example, in the Qur'an are interpreted differently according to the context of the sentence. The use of the word fi’il related to the process of seeing are abshara, ra’a, nadzara, and anasa; related to the hearing processare, are sami’a, anshata, ashgha; related to the process of feeling, are dzaqa, tha’amaandakala, and relating to the fingering, which allegedly lamisa and massa are assumed to have different meanings based on its context. To covert the meanings, semantic approach in content analysis method was used. The implications are the development of the five sense competence is very important to do to lead people to have perfect personality.